Sistem Peradilan Edukatif Dalam Sistem Peradilan Anak Di Indonesia - Harahap, Asliani (DE LEGA LATA: JURNAL ILMU HUKUM, 2018)
Educative judicial system must be the priority of the judge in making a decision. Placing children in prison will always be the last choice with the shortest possible period of time. Placing children in institutions that have social benefits and functions as well as improvements for children is better, but it is hoped that these institutions can provide care, protection, education and special skills that are educational in nature so that they can be used to help them social construction and productive in the community. The educational punishment system in the juvenile court system in its application is beneficial to children as perpetrators of crimes, which is expected in the protection of children as perpetrators of criminal offenses should receive serious attention from the government. Children who are compliant with the law in the position of children as perpetrators of crime, in addition to needing protection and self-security also require legal regulations that guarantee the interests of children. The benefit for children as perpetrators of crime is that the development of the child's soul is not disturbed and for the protection and interests of the child.